Role of Ultrasound Elastography in Differentiating Pancreatic Cancer: Present and Future Directions - Jankowska, Justyna; Marciszuk, Szymon; Olejnik, Agnieszka; Zdaniewicz , Mateusz; Rataj, Jonatan; Budzik, Paweł; Jagura-Sukiennik , Aleksandra; Stolarczyk , Magdalena; Bezak, Julia; Radzka, Marlena; et al. (Quality in Sport, 2026)
Aim. To review the diagnostic value of ultrasound elastography in the assessment of focal pancreatic lesions, particularly its role in differentiating benign from malignant lesions during endoscopic ultrasound (EUS) examinations. Materials and Methods. A narrative review of published studies on ultrasound elastography techniques, including strain elastography (SE), acoustic radiation force impulse (ARFI), and shear wave elastography (SWE), was conducted. The analysis focused on elastography parameters such as strain ratio (SR), strain histogram (SH), and shear wave velocity (SWV), as well as their reported diagnostic performance in pancreatic imaging. Results. Ultrasound elastography allows non-invasive assessment of tissue stiffness, with malignant pancreatic lesions generally demonstrating higher stiffness than benign or inflammatory lesions. Studies report high sensitivity of EUS elastography for detecting malignancy (approximately 90–97%) with diagnostic accuracy around 87–89%, although specificity remains moderate. Quantitative techniques such as SWE provide more reproducible measurements than qualitative strain-based assessment. Emerging approaches combining elastography parameters with artificial intelligence and radiomic analysis show potential to further improve diagnostic accuracy. Conclusion. EUS elastography is a useful complementary technique in the evaluation of focal pancreatic lesions. Although it cannot replace biopsy due to limited specificity, it may improve lesion characterisation and help target the most suspicious areas for tissue sampling. Future integration with artificial intelligence may further enhance diagnostic performance.